Trapping of Carboxylic Oxonium Ylides with N-Boc Imines for the Facile Synthesis of β-Amino Alcohol Derivatives - Zhai, Changwei; Xing, Dong; Qian, Yu; Ji, Jingjing; Ma, Chaoqun; Hu, Wenhao (Synlett, 2014)
A Rh2(OAc)4-catalyzed three-component reaction of carboxylic acids, α-diazoacetophenones, and N-Boc imines has been developed to efficiently produce β-amino alcohol derivatives. Oxonium ylides generated from carboxylic acids and metal carbenoids have been intercepted by electrophiles for the first time.
Keywords: multicomponent reactions; diazo compounds; metal carbenoids; ylides; imines